Towards more comprehensive measures of social support: adding in the impact of taxes and private Spending or netting out the impact of politics on redistribution? - Francis G. Castles; Herbert Obinger (Universität Bremen, Zentrum für Sozialpolitik (ZeS), 2006)
This paper offers a critique and analysis of recent OECD research by Adema and Ladaique identifying the impact of taxes and private benefits on social spending. Using the techniques of multivariate modelling, we show that both gross public and net private expenditures are strongly influenced by partisan incumbency, although in opposite directions, and that the more we net out the effect of taxes, the less politics matters and the more spending is shaped by economic forces. In a second stage of the analysis, we show that the crucial mechanism of welfare state redistribution is the taxation of gross social expenditure and demonstrate that this effect is almost entirely political in nature.
Keywords: 320